Atomic Habits, Mental Health, and Poverty Reduction: Adaptive Ritual Practices in Bali - Surya Pradnya, I Made Adi; I Made Danu Tirta,; I Putu Andre Suhardiana,; Thanakorn Choosukhserm, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
The practice of Balinese Hinduism is increasingly challenged by the economic costs of ritual obligations, contributing to ritual-induced poverty and associated mental health burdens. Although previous studies have documented these problems, little attention has been paid to practical solutions. This qualitative study examines alternative forms of yadnya rituals in Bali that reduce both economic and psychological burdens. Data were collected through interviews, participant observation, and document analysis involving ritual practitioners, crematorium managers, griya priests, and religious leaders in Bangli, Denpasar, Gianyar, and Karangasem. The analysis identifies four adaptive practices: alternative ritual venues, crematorium-based ceremonies, digital technologies, and collective rituals. These innovations reduced ritual costs by approximately 90-97% while alleviating psychological distress associated with social expectations and financial pressure. This study contributes by demonstrating that theological reinterpretation by religious leaders enables communities to preserve ritual values while adapting to contemporary economic and mental health challenges.
Keywords: yadnya; Balinese Hinduism; mental health; poverty reduction; atomic habits